A Case Report of a Female Patient With Hodgkin Lymphoma Localized in the Central Nervous System and With Concomitant Pulmonary Lymphomatoid Granulomatosis - Szczepanek, Dariusz; Szumiło, Justyna; Stoma, Filip; Szymczyk, Agnieszka; Jarosz, Bożena; Szczepanek, Aleksandra; Hus, Marek; Trojanowski, Tomasz; Wasik-Szczepanek, Ewa (Frontiers in Neurology, 2020)
The involvement of the central nervous system (CNS) in Hodgkin lymphoma (HL) has been rarely reported, especially in its primary isolated form. Herein, we present a case of a 33-year-old woman, who received immunosuppressive treatment due to colitis ulcerosa (at the beginning azathioprine and sulfasalazine, changed to mesalazine), with repetitive episodes of loss of consciousness for a few weeks and with no other symptoms. Magnetic resonance imaging scans of the head revealed a tumor in the lateral part of the left temporal lobe and in the cerebellum. Moreover, a subsequent computed tomographic scan of the chest revealed diffuse tumorous lesions in the lungs. The brain tumor was resected and a tumorous lesion resected from the lungs was biopsied. The histopathological analysis confirmed the final diagnosis of HL localized in the CNS with concomitant pulmonary lymphomatoid granulomatosis (LYG) grade 1. After the patient underwent radiotherapy and chemotherapy, the patient showed complete regression of lesions in the CNS and lungs, which was confirmed by positron emission tomographic scan. LYG and CNS-HL are rare proliferative disease derived from lymphocytes B and associated with EBV infections. An association between LYG and other autoimmune disorders has been reported, but to the best of our knowledge, this is the first case of the CNS-HL associated with lymphatoid granulomatosis.